SIFAT KIMIA DAN TINGGI MUKA AIR TANAH GAMBUT PADA TIGA TIPE PENGGUNAAN LAHAN DI FISIOGRAFI KUBAH GAMBUT DAN RAWA BELAKANG KHG KAHAYAN-SEBAGAU - Marinus Kristiadi Harun; Syaiful Anwar; Eka Intan Kumala Putri; Hadi Susilo Arifin (Lambung Mangkurat University-Indonesia, 2020)
This study aims to: (1) determine the chemical properties of peat soils in 3 types of land cover in 2 physiographies; (2) find out water level fluctuations (WLF) on peat soils covered by agroforestry and horticulture in the physiography of peat dome and backswamp during the rainy season, transitions and drought. This research was conducted in January until December 2018 in Kahayan-Sebangau Peat Hidrological Unit, in the Kalampangan Vilagge. The results showed that differences in peat soil cover conditions at different physiographies affected chemical properties and WLF. The three types of peatland cover on both physiographic types of peatlands have a pH that categories into the very acid (<4.5). The results of this study indicate that nutrients (N, P, Kd, C, Mg, Al, Na and SO4) that are formed in each type of land cover in 2 physiographies indicate that these elements in peatlands are influenced by a layer of peat which obtains input of organic material from the plants above it. Peat fertility depends on the contribution of organic material from plants on it. Peatland cation exchange capacity values for all types are in the very high category (> 40). In addition to the chemical elements of the soil, the peat ground water level is highly volatile following rainfall so that during the peak of the dry season (MK) the WLF can reach 200 cm below the ground surface, and vice versa during the peak of the rainy season (MH) the WLF can inundate all peat soils.